2015
DOI: 10.1364/ao.55.000104
|View full text |Cite
|
Sign up to set email alerts
|

Dual wavelength laser-induced damage threshold measurements of alumina/silica and hafnia/silica ultraviolet antireflective coatings

Abstract: An approach for the measurement of the laser-induced damage threshold with two wavelengths combined was made while testing antireflective coatings for the wavelengths 266 and 532 nm. Samples were made of Al2O3/SiO2 and HfO2/SiO2 ion beam sputtered films. The results show that adding radiation of a second wavelength might lead to a significant reduction of the threshold. The damage morphology of single and dual wavelength tests is very similar and does not suggest an altered damage mechanism. Further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Laser-induced periodic surface structure (LIPSS) formation on metals [17,18], semiconductors [19] and dielectrics [20,21] has been intensively investigated by the two-colour (UV-IR) double-pulse femtosecond laser irradiation. The two-colour double-pulse irradiation has been used for laser-induced damage threshold (LIDT) testing of optical coatings [22][23][24][25], and has proved to reduce the damage threshold by 71% for Al 2 O 3 coating [26]. Better control in the energy deposition has been demonstrated during dual-wavelength double-pulse laser machining of dielectrics [27].…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced periodic surface structure (LIPSS) formation on metals [17,18], semiconductors [19] and dielectrics [20,21] has been intensively investigated by the two-colour (UV-IR) double-pulse femtosecond laser irradiation. The two-colour double-pulse irradiation has been used for laser-induced damage threshold (LIDT) testing of optical coatings [22][23][24][25], and has proved to reduce the damage threshold by 71% for Al 2 O 3 coating [26]. Better control in the energy deposition has been demonstrated during dual-wavelength double-pulse laser machining of dielectrics [27].…”
Section: Introductionmentioning
confidence: 99%
“…The laser-induced periodic surface structure (LIPSS) or ripple formation by the two-colour (UV-IR) double pulse femtosecond laser irradiation on conductors 20, 21 semiconductors 22 and dielectrics 23 has been intensively investigated 24 . The two-colour double-pulse irradiation has been used for laser induced damage thresholds (LIDT) of coatings 25–28 and has proved to reduce the damage threshold by 71% for Al 2 O 3 coating 29 . It has been demonstrated that dual-wavelength double pulse laser machining is an efficient way to improve the laser processing of dielectrics by providing a better control of the energy deposition process 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In modern laser systems, optical surfaces may be operated at different wavelengths simultaneously. Recent studies [52,53] imply a significant reduction of the damage thresholds at the individual wavelengths for such operation conditions. Consequently, the power handling capability of a specific component will be overestimated, if the threshold values for single wavelength operation are presumed for the design of laser systems.…”
mentioning
confidence: 99%